2011
DOI: 10.5194/hess-15-989-2011
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic similarity among catchments under variable flow conditions

Abstract: Abstract. An assessment of regional similarity in catchment stream response is often needed for accurate predictions in ungauged catchments. However, it is not clear whether similarity among catchments is preserved at all flow conditions. We address this question through the analysis of flow duration curves for 25 gauged catchments located across four river basins in the northeast United States. The coefficient of variation of streamflow percentiles is used as a measure of variability among catchments across f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…6) illustrates the preference of high predictability catchments towards humid regions. Our previous work (Patil and Stieglitz, 2011) characterized streamflow similarity among nearby catchments across multiple flow conditions. Patil and Stieglitz (2011) suggested that the competing influences of precipitation input and evaporative demand determine the conditions at which regional streamflow similarity is manifested.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6) illustrates the preference of high predictability catchments towards humid regions. Our previous work (Patil and Stieglitz, 2011) characterized streamflow similarity among nearby catchments across multiple flow conditions. Patil and Stieglitz (2011) suggested that the competing influences of precipitation input and evaporative demand determine the conditions at which regional streamflow similarity is manifested.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work (Patil and Stieglitz, 2011) characterized streamflow similarity among nearby catchments across multiple flow conditions. Patil and Stieglitz (2011) suggested that the competing influences of precipitation input and evaporative demand determine the conditions at which regional streamflow similarity is manifested. Consistent with their suggestion, the results presented here show that streamflow similarity among nearby catchments is more likely to occur in regions where annual precipitation exceeds evaporative demand (i.e., low energy environments).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Values of α Q tending to 0 indicate strongly correlated data, values close or higher than 1 show absence of correlation. Actually, the analysis of the correlation structures would require stationary time series, whereas streamflow observations (as well as rainfall ones) exhibit a strong dependency on the season (see also the recent analysis by Patil and Stieglitz, 2011); to solve this problem, the above cited papers assume stationarity on a seasonal basis, estimating separate coefficients for the different seasons or months. In addition, if trends were present, Eq.…”
Section: Streamflow Signaturesmentioning
confidence: 99%
“…Nathan and McMahon, 1990;Laaha and Bloeschl, 2006;Vezza et al, 2010) or the entire flow duration curve (e.g. Singh et al, 2001;Ley et al, 2011;Patil and Stieglitz, 2011;Sauquet and Catalogne, 2011). On the other hand, such representations do not allow to take into account the sequential order and the stochastic nature of the streamflow process; these properties would, for example, be crucial if the regionalisation aimed, as often needed in the hydrological practice, at the parameterisation of a rainfall-runoff model at fine temporal scale and the catchment similarity should therefore be guaranteed in terms of continuous streamflow generation.…”
Section: E Toth: Catchment Classificationmentioning
confidence: 99%